Reconstruction of Digital Evidence Models in Cybercrime: An Integrative Analysis of Contemporary Criminology and Digital Forensics - Rachmat Alviando; Herlita Eryke (UNIVERSITAS PAKUAN, 2026)
The rapid development of information technology has changed the social and economic landscape, while introducing complex challenges in the form of cybercrime, which is often difficult to handle using conventional legal evidence mechanisms. This study aims to develop and test a conceptual model that links perpetrator criminogenic factors, the application of digital forensics, and regulatory or institutional power with the success of digital evidence in cybercrime cases. To address this issue, a quantitative approach with a correlational design was used, with data collected through a purposive sampling survey of 120 law enforcement practitioners and digital forensic experts in Indonesia. The results show that the application of digital forensics (β = 0.45, p < 0.001) and regulatory strength (β = 0.28, p < 0.01) significantly incrRRease the success of digital evidence, while perpetrator criminogenic factors and complex modus operandi have a negative influence (β = –0.22, p < 0.05). Analysis of these findings suggests that the success of digital evidence is highly dependent on the integration of technical-forensic precision with institutional support to counter the increasing complexity of anti-forensic techniques used by criminals. Based on this analysis, it is recommended that law enforcement agencies strengthen the capacity of digital forensic laboratories and harmonize legal regulations to be more adaptive to the dynamic nature of cyber threats and technological advances.